Spór o multipleks. Telewizja Trwam kontra Krajowa Rada Radiofonii i Telewizji - Secler, Bartłomiej (Przegląd Politologiczny, 2018)
The digitalization of terrestrial television in Poland is one of the largest media projects in recent years. The process combines social, economic and technical matters. Digitalization signifies a huge technical leap forward and offers extensive new opportunities when broadcasting television signals. Digital broadcasting is offered by three multiplex platforms. Among the candidates to use the first one (MUC-1) is Telewizja Trwam, owned by the Lux Veritatis foundation. The National Broadcasting Council (KRRiT) which assigns the concessions to use the multiplex rejected the application by Telewizja Trwam, associated with Fr. Tadeusz Rydzyk. The owner of Telewizja Trwam claimed the decisions of the KRRiT were baseless. There quickly emerged accusations of discrimination against a Catholic broadcaster, and, by this token, of scorn directed toward Polish Catholics. The dispute between Telewizja Trwam and the KRRiT has involved many groups and individuals – ranging from the supporters of the media associated with Fr T. Rydzyk, to journalists, politicians, and to the hierarchy of the Catholic Church in Poland. The purpose of this paper is to present this dispute, its background and the arguments of both parties. As the dispute was still unresolved when this paper was completed (in late February 2013), the author tried to suggest possible scenarios for its outcome and to draw conclusions for the future.